2008
DOI: 10.1021/jp801103n
|View full text |Cite
|
Sign up to set email alerts
|

Fibronectin Adsorption on Tantalum: The Influence of Nanoroughness

Abstract: The complex mechanisms of protein adsorption at the solid-liquid interface is of great importance in many research areas, including protein purification, biocompatibility of medical implants, biosensing, and biofouling. The protein adsorption process depends crucially on both the nanoscale chemistry and topography of the interface. Here, we investigate the adsorption of the cell-binding protein fibronectin on flat and nanometer scale rough tantalum oxide surfaces using ellipsometry and quartz crystal microbala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
82
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(93 citation statements)
references
References 53 publications
9
82
0
2
Order By: Relevance
“…At t = 220 min, after the PBS rinse, the GE and QCM-D surface density values are approximately 14.3 mg/m 2 and 14.1 mg/m 2 , respectively. In contrast, Hovgaard et al reported an ellipsometry-derived surface density of approximately 2 mg/m 2 ; their result is in agreement with a null ellipsometry experiment by Ivarsson and Lundström for FN adsorption onto flat Ti [21,22].…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…At t = 220 min, after the PBS rinse, the GE and QCM-D surface density values are approximately 14.3 mg/m 2 and 14.1 mg/m 2 , respectively. In contrast, Hovgaard et al reported an ellipsometry-derived surface density of approximately 2 mg/m 2 ; their result is in agreement with a null ellipsometry experiment by Ivarsson and Lundström for FN adsorption onto flat Ti [21,22].…”
Section: Resultssupporting
confidence: 75%
“…5 shows similar frequency and dissipation values as seen for FN adsorption on flat Ta by Hovgaard et al We consider the similarity noteworthy because the surface geometries are significantly different between the experiments. The dissipation shifts are very small compared to the frequency shifts, and as Hovgaard et al did, we assume a rigid FN layer [22]. Equation (3) was applied to the third harmonic overtone to yield Γ QCM over a reference flat surface.…”
Section: Resultsmentioning
confidence: 99%
“…fibronectin and collagen) and cell surface receptors. The different doped films also have varying surface roughness, ranging from ≈ 6 -100 nm RMS (over 10 um area), that is a mitigating factor known to affect protein-biomaterial interactions 43 . Nanoscale surface roughness particularly influences the adsorption of large proteins such as FN and fibrinogen 43,44 , however, its effects are varied and generalization of relationship between roughness and protein adsorption is difficult.…”
Section: Resultsmentioning
confidence: 99%
“…The different doped films also have varying surface roughness, ranging from ≈ 6 -100 nm RMS (over 10 um area), that is a mitigating factor known to affect protein-biomaterial interactions 43 . Nanoscale surface roughness particularly influences the adsorption of large proteins such as FN and fibrinogen 43,44 , however, its effects are varied and generalization of relationship between roughness and protein adsorption is difficult. Recent QCM studies on FN adsorption to PPy/DS showed increased adsorption on more hydrophilic films with higher dopant concentration yet no surface morphology-induced effects on the protein adsorption was observed 22 .…”
Section: Resultsmentioning
confidence: 99%
“…5 Recently, it has been reported that surfaces with nano features, either disordered 6,7 or ordered (e.g. gold nanoparticle arrays, 8 titanium nanotube arrays, [9][10][11][12] chemically etched titanium surfaces, 13,14 and nanostructured tantalum surfaces) [15][16][17] can greatly improve cell adhesion, proliferation and differentiation. 18 Our group has developed a general nano-patterning method for metal surfaces that is inexpensive as well as time-efficient.…”
Section: Introductionmentioning
confidence: 99%